Hirsutism or Hyperandrogenemia, Which is More Noteworthy for Adolescent Girls with Irregular Menses? A Case–Control Study Based on an Epidemiological Survey - Yu Hong; Lili Huang; Dongzi Yang; Zehong Zhou; Zhe Dong (Women's Health Reports)
Background: Polycystic ovarian syndrome (PCOS) develops from early puberty on and progresses afterward, and a persistent hyperandrogenic state puts adult PCOS patients at risk of metabolic abnormality. If hyperandrogenism-related metabolic problems can be detected early in adolescence, it could have a quite positive impact on patients’ reproductive health and cardiovascular disease prevention in the future. Accordingly, this study was performed to delineate the clinical and biochemical hyperandrogenic status of adolescents with irregular menses, and to explore which one was more noteworthy in this population. Method: Based on the questionnaire of an epidemiological survey carried out by our research team, this case–control study compared the anthropomorphic, clinical, and laboratory materials of adolescent girls, at least 2 years after menarche, with irregular menses, as well as those with regular periods. Androgen and metabolism-related indicators were measured in their serum samples. Simultaneously, they were categorized and compared based on whether they presented with hirsutism (mFG ≥6). Results: There were no significant differences in serum androgen parameters between the hirsute and nonhirsute groups. The mFG score was found to be slightly positively correlated with A2 and dehydroepiandrosterone sulfate (DHEAS), and there was no significant correlation with other clinical and androgenic indicators. There were no significant differences in various clinical indicators, serum androgens, or the incidence of hirsutism between girls with oligo-/amenorrhea and girls with normal menses. When compared to girls with normal menses, those with oligo-/amenorrhea were more likely to have a higher risk of developing biochemical hyperandrogenism [odds ratio (OR) = 1.961 (1.131–3.401), p = 0.021], and had a similar prevalence of hirsutism [OR = 0.651(0.314–1.352), p = 0.294]. Body mass index (BMI), waist circumference, waist–hip ratio, diastolic blood pressure, fast insulin (FIN), triglyceride (TG), cholesterol (CHOL), and low density lipoprotein (LDL) of PCOS group and hyperandrogenism-only group were slightly higher than those of the control group. Within the PCOS group, the BMI, systolic blood pressure (SBP), FIN, TG, and CHOL of patients with biochemical hyperandrogenism were slightly higher than those in clinical hyperandrogenism. The incidence of hyperinsulinemia, overweight, or obesity in the PCOS group was significantly higher than that in the control group (p < 0.05), and there was no significant difference in the incidence of different types of hyperlipidemia, central obesity, or elevated blood pressure between the two groups (p > 0.05). Conclusion: At least 2 years after menarche, adolescent girls with oligo-/amenorrhea are more likely to have concomitant biochemical hyperandrogenism than those with hirsutism. In this population, those with hirsutism or hyperandrogenemia present a higher incidence of some metabolic abnormalities, such as hyperinsulinemia and being overweight or obese.